Islamic branding: the understanding and perception - Mohd Yusof, Y. L.; Wan Jusoh, Wan Jamaliah (Elsevier, 2014)
There is such confusion and improper use of the term of Islamic branding and until now there seems to be no clear understanding of what the term Islamic branding means. Therefore to avoid such confusion the term Islamic branding was analyzed by several scholars and this study aims to identify Muslim consumer’s perception and understanding of Islamic brands. 20 respondents were selected, which is Segment 1 were 8 females and 2 males. Meanwhile respondents from Segment 2 were 5 females and 5 males that are from various industries such as manufacturing, banking, education and plantation. Segment 1 consisted of students aged 20 to 26 years old and Segment 2 was adult working respondents aged 35 to 50 years old. From the focus group findings disclosed that most of consumers agreed that the Islamic branding defines as a product or service that meets the Sharia-compliant and any parties that involved in Halal accreditations should be seriously implemented strict procedures to the producers in getting the Halal logo. Additionally, significantly in promoting and improving the Islamic brands to the consumers, producers or marketers need to follow all the requirements that required by authorization bodies either in organization’s practices and branding features to obtain consumer’s trust and confidence upon Islamic branding.